Infant Formula With a Specific Blend of Five Human Milk Oligosaccharides Drives the Gut Microbiota Development and Improves Gut Maturation Markers: A Randomized Controlled Trial - Bosheva, Miroslava; Tokodi, Istvan; Krasnow, Aleksander; Pedersen, Helle Krogh; Lukjancenko, Oksana; Eklund, Aron C.; Grathwohl, Dominik; Sprenger, Norbert; Berger, Bernard; Cercamondi, Colin I.; , 5 HMO Study Investigator Consortium; Bauer, Viktor; et al. (Frontiers in Nutrition, 2022)
Background: Human milk oligosaccharides (HMOs) have important biological functions for a healthy development in early life. Objective: To investigate gut maturation effects of infant formula containing five HMOs (2'-fucosyllactose, 2',3-di-fucosyllactose, lacto-N-tetraose, 3'-sialyllactose, 6'-sialyllactose). Methods: In a multicenter study, healthy infants (7-21 days old) were randomly assigned to a standard cow’s milk-based infant formula (control group, CG); the same formula with 1.5 g/L HMOs (test group 1, TG1); or with 2.5 g/L HMOs (test group 2, TG2). A human milk-fed group (HMG) was enrolled as reference. Fecal samples collected at baseline (n~150/formula group; HMG n=60), age three (n~140/formula group; HMG n=65) and six (n~115/formula group; HMG n=60) months were analyzed for microbiome (shotgun metagenomics), metabolism and biomarkers. Results: At both post-baseline visits, weighted UniFrac analysis indicated different microbiota compositions in the two test groups (TGs) compared to CG (P<0.01) with coordinates closer to that of HMG. Relative abundance of Bifidobacterium longum subsp. infantis (B. infantis) was higher in TGs vs. CG (P<0.05; except at 6-month: TG2 vs. CG P=0.083). Bifidobacterium abundance was higher by 45% in TGs vs. CG at 6-month approaching HMG. At both post-baseline visits, toxigenic Clostridioides difficile abundance was 75-85% lower in TGs vs. CG (P<0.05) and comparable with HMG. Fecal pH was significantly lower in TGs vs. CG and the overall organic acid profile was different in TGs vs. CG, approaching HMG. At 3-month, TGs (vs. CG) had higher secretory immunoglobulin A (sIgA) and lower alpha-1-antitrypsin (P<0.05). At 6-month, sIgA in TG2 vs. CG remained higher (P<0.05) and calprotectin was lower in TG1 (P<0.05) vs. CG. Conclusions: Infant formula with a specific blend of five HMOs supports development of the intestinal immune system and gut barrier function and shifts the gut microbiome closer to that of breastfed infants with higher bifidobacteria, particularly B. infantis, and lower toxigenic Clostridioides difficile. Clinical trial registration: NCT03722550 (https://clinicaltrials.gov/ct2/show/NCT03722550)